Edukasi dan Pemberdayaan Masyarakat dalam Pembuatan Jamu Instan Kunyit dan Temulawak sebagai Penambah Nafsu Makan - Ilmawati, Eldesi Medisa; Rangkuti, Meili Savitri (Cattleya Darmaya Fortuna, 2025)
This community service activity aims to provide education and empowerment in the production of instant dry herbal medicine (jamu) made from turmeric (Curcuma domestica Val.) and Javanese ginger (Curcuma xanthorrhiza Roxb.) as appetite stimulants. Family medicinal plants (TOGA) such as turmeric and Javanese ginger have significant potential as phytopharmaceutical raw materials, particularly for naturally enhancing appetite, yet they are rarely utilized optimally by the community. This activity was implemented through lectures, outreach, and hands-on practice involving local community partners. The material provided included an introduction to the active ingredients and benefits of both plants, as well as training in making instant herbal medicine in the form of a water-soluble powder. The activity results showed a 75% increase in participants' knowledge based on pre- and post-test evaluations. Furthermore, participants were able to independently produce instant herbal medicine using simple techniques and expressed interest in developing this product as a home business. This activity demonstrates that education combined with practical application can increase the use of local medicinal plants and encourage community independence in managing family health and herbal-based economics.